2019
DOI: 10.1177/1933719118820474
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pregnancy Outcomes in Patients Undergoing Donor Egg Single Embryo Transfers With and Without Preimplantation Genetic Testing

Abstract: Two of the many milestone developments in the field of assisted reproduction have been oocyte donation and preimplantation genetic testing for aneuploidy (PGT-A). Because it has been demonstrated that even young women produce a meaningful proportion of aneuploid embryos, screening out such abnormalities could potentially increase the efficacy of donor egg (DE) cycles. In this retrospective cohort study, we investigated the effect of PGT-A on DE cycle outcomes, including implantation rate (IR), spontaneous abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
2
14
2
Order By: Relevance
“…No difference in euploidy rate among the interval of donor ages was observed in this study [16]. Furthermore, IVF cycle outcomes of younger women with no PGT-A indications do not seem to benefit from having it performed [2,9,17,18]. This lack of benefit also applies to young patients in the same age range as donors using autologous oocyte cycles.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…No difference in euploidy rate among the interval of donor ages was observed in this study [16]. Furthermore, IVF cycle outcomes of younger women with no PGT-A indications do not seem to benefit from having it performed [2,9,17,18]. This lack of benefit also applies to young patients in the same age range as donors using autologous oocyte cycles.…”
Section: Discussionmentioning
confidence: 57%
“…Despite the high success rates of OD cycles, some patients still perform PGT-A on their embryos as they feel it will increase their chances of getting pregnant and delivering a healthy baby. Previous paired cohort studies have shown that genetic testing in oocyte donor-recipient cycles is not associated with increased successful pregnancy and birth rates [7][8][9][10]. However, the results of these studies are exclusively based on cryopreserved OD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Donor eggs are usually collected from healthy, young, and fertile women, hoping that most eggs will have normal chromosomal integrity. When considering literature data presented in the previous chapters of this review, it can be affirmed that even young women produce a significant proportion of aneuploid embryos and screening out such abnormalities could potentially increase the efficacy of donor egg (DE) cycles [146].…”
Section: Pgt-a In Donor Egg Cyclesmentioning
confidence: 95%
“…These findings suggest that PGT-A might only be necessary in some specific situations, such as the need of a single embryo transfer. In 2019, Masbou et al [146] compared, in a retrospective cohort study, clinical outcomes in patients undergoing ED cycle with SET with and without pre-implantation genetic testing. This study revealed that PGT-A and subsequent euploid SET did not improve pregnancy outcome in DE cycles, although there was a trend toward decreasing of miscarriage rate.…”
Section: Pgt-a In Donor Egg Cyclesmentioning
confidence: 99%
“…Studies have estimated that approximately 12% of married women have difficulty getting pregnant or maintaining a pregnancy ( 1 ). Even with the latest whole-genome sequencing technology to select the high quality embryo, the pregnancy rate for euploid embryo transfer has been found to be approximately 45% in the general infertility population ( 2 , 3 ) and approximately 60% in patients with donor egg embryos ( 4 ) undergoing in vitro fertilization-embryo transfer (IVF-ET)practices. In recent years, researchers have focused on the role of endometrium in infertility, assuming that endometrial dysfunction might contribute to a large part of pregnancy failure.…”
Section: Introductionmentioning
confidence: 99%